SCIENCE AND SPIRITUALITY IN CHAGANIYAN - Ergashev Mavlon Eshniyozovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In this article, In the 10th-11th centuries, Chaganion became one of the major cultural centers of Central Asia. Along with the socio-economic development of the country, this was caused by the great care of Chaganiyan emirs for the development of science and culture.